The Effects of Environmental Consciousness in Public Healthcare Institutions and Community Awareness in Mokwa Local Government Area, Niger State, Nigeria - Ja’agi, Idris, Aliyu; Baba, J.M; Y. M., Suleiman (Journal of Environments, 2015)
The effects of environmental consciousness in public healthcare institutions and the community awareness of the impacts were investigated. Environmental Pollution resulting from healthcare operations are a major problem in Mokwa Local Government Area LGA as the hospital material output goes directly to the environment without check. Similar situation has been reported in developing world. The objective is to find the opportunity for healthcare sector to improve on the overall environmental performance. Collated data was analyzed using simple percentage analysis. Results of the findings shows that the management of the healthcare institutions investigated have not taken into cognizance the environmental implication of the material input and output, lack effective environmental management system and poor environmental condition within and the environs. It is recommended that effective environmental management system be put in place. Also, government dedication, and collective responsibility of relevant stakeholders toward managing the environmental aspects and impacts of the health care institutions in the study area are critical for improvement. These will guarantee cleaner and healthier environment for all.